Effects of buddleja officinalis total flavonoids on serum testosterone level of castrated male rats with xeroma - Wen-Juan Li (Guoji Yanke Zazhi, 2013)
AIM:To observe buddleja officinalis total flavonoids' effect on the basal tear secretion amount, tear film stability, lacrimal gland histomorphology and serum testosterone level of castrated male rat model with xeroma, to study the mechanism of rat xeroma caused by buddleja officinalis total flavones' anti-sex hormones disorders. MEATHODS: A total of 150 Wistar male rats of 1 month old, weighted about 200g, were randomly divided into 5 groups with 30 rats in each group with A representing normal group; B representing sham operation group; C representing surgery control group; D representing group treated with androgen; E representing group treated with buddleja officinalis total flavonoids. For the groups C, D, E, the bilateral testicle and epididymis were excised; For group B, scrota were incised without removal of the testicles, as the sham operation group; For group A, nothing was done. One week after modeling when the wound was to be healed, drug was given to each group. Respectively at the 1st month, 3rd, and 5th months after treatment, 10 rats were randomly selected in each group, to receive Schirmer I test, tear breakup time measurement. Blood serum testosterone levels were tested in the fifth month. RESUITS: For groups D and E, the Schirmer I test measurements were significantly higher than that of group C(P<0.05), tear film breakup time was significantly longer than that of group C(P<0.05). Serum testosterone levels in groups C and E were significantly lower than that in groups A, B, D(P<0.01). CONCLUSION: Decreased androgen levels can lead to xeroma, and removal of bilateral testes and epididymis can successfully establish the animal models of xeroma in rats caused by decreased androgen levels. Buddleja officinalis total flavonoids have androgenic effect, which produces the similar treatment effect of xeroma with testosterone propionate. Buddleja officinalis total flavonoids may become a new treatment for xeroma.